2005
DOI: 10.1152/ajpregu.00405.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute hyperinsulinemia on insulin signal transduction and glucose transporters in ovine fetal skeletal muscle

Abstract: . Effects of acute hyperinsulinemia on insulin signal transduction and glucose transporters in ovine fetal skeletal muscle. Am J Physiol Regul Integr Comp Physiol 288: R473-R481, 2005. First published November 11, 2004; doi:10.1152/ajpregu.00405.2004.-To test the effects of acute fetal hyperinsulinemia on the pattern and time course of insulin signaling in ovine fetal skeletal muscle, we measured selected signal transduction proteins in the mitogenic, protein synthetic, and metabolic pathways in the skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
(58 reference statements)
1
17
1
Order By: Relevance
“…Previous studies in late-gestation fetal sheep have shown that acute hyperinsulinemia at pharmacological doses (ϳ110 U/ml) activates the insulin signal transduction pathway through PI3-kinase/Akt, leading to substantial upregulation of p70 S6k and 4E-BP1 and assembly of the translation initiation complex eIF4F (2,40). Consistent with these results, we found a sevenfold increase in the phosphorylation of Akt, p70 S6k , and rp S6 with high-dose fetal insulin infusion.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in late-gestation fetal sheep have shown that acute hyperinsulinemia at pharmacological doses (ϳ110 U/ml) activates the insulin signal transduction pathway through PI3-kinase/Akt, leading to substantial upregulation of p70 S6k and 4E-BP1 and assembly of the translation initiation complex eIF4F (2,40). Consistent with these results, we found a sevenfold increase in the phosphorylation of Akt, p70 S6k , and rp S6 with high-dose fetal insulin infusion.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, an increase in GLUT 4 concentrations of the extensor digitorum lateralis and biceps femoris muscles was observed. Although the changes in GLUT concentrations that we observed were not large, previous work by some of us has demonstrated that even small changes in GLUT concentrations in the ovine fetus can have a major impact on fetal glucose homeostasis (Anderson et al 2005).…”
Section: Discussioncontrasting
confidence: 76%
“…There are several possible mechanisms to account for this observation. First, fetal insulin concentrations as a result of the insulin infusion were much higher than those achieved in previous studies, and, by study design, the infusion period was for a shorter duration to capture acute upregulation of signal transduction in muscle (2). Moreover, the marked increase in fetal insulin concentrations achieved by the insulin clamp, while stimulating protein translation capacity in skeletal muscle, may not promote net protein turnover along the same time frame in the whole animal.…”
Section: Discussionmentioning
confidence: 88%